Hematological and Biochemical Changes in Female Type 2 Diabetes Mellitus (T2DM) Patients Attending a Tertiary Care Hospital - Iqbal, Uzair; Shahid, Amen; Hamid, Mohsina; Malik, Shakoor Ahmad; Memon, Mahak; Ibadin, Shelly (Journal of Neonatal Surgery, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is an intricately complex and heterogeneous disorder with the possibility of impacting multiple organ systems. While formulating a glycemic control strategy the hematological and biochemical alterations in diabetes patients are neglected, more so in women, where the presentation may be subtle and diffuse modifications of a more global nature. Evaluate the hematological and biochemical abnormalities in women with Type 2 Diabetes Mellitus attending a tertiary care hospital. Methods: A cross-sectional study was conducted between august 2023 and September 2024, enrolling 81 female patients with type 2 diabetes mellitus (T2DM). The study assessed hematological parameters like hemoglobin, red cell indices, ESR, along with biochemistry markers such as glucose, HbA1c, lipid profile and renal function assessment both in fasting and postprandial states. Data were analyzed using SPSS version 25 and a p-value of less than 0.05 was considered significant. Results: Participants showed common instances of anemia alongside an elevated ESR, with notable reductions in hemoglobin, MCH, MCHC, and an increase in RDW. Marked elevation of glycemic indices also pointed towards an inadequately controlled diabetes mellitus. There were striking features of dyslipidemia as well which included elevated triglycerides and LDL alongside decreased levels of HDL cholesterol. The participants' renal and hepatic parameters remained largely within normal limits. Conclusion: Female T2DM patients exhibit a range of hematological and biochemical alterations, suggesting systemic involvement beyond hyperglycemia. Routine evaluation of these parameters may assist in early detection of complications and guide comprehensive diabetes management strategies..